Pengembangan Usaha Food Court Dalam Pembangunan Ekonomi Daerah di Kabupaten Jeneponto - Abdul Malik Habir (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2025)
Micro, Small and Medium Enterprises (MSMEs) consist of several business sectors, one of which is the culinary business sector. One type of culinary business that is currently developing is the Food Court business, Food Court is a place to eat with counters or stalls consisting of various food vendors and provided a common area for self-serve dining. from the conclusion that the role of the local government in developing the food court business has not been implemented properly and the positive impact of this development is felt by the community, especially for business actors in Goedang kapas. The negative impact is that the impact of Food Court type MSMEs especially in Goedang Kapas in economic development in Jeneponto Regency does not have a significant influence between the increase in per capita income and the development that occurs in Food Court type MSMEs especially in Goedang Kapas